Evaluation of collection accessions of fiber flax according to flax fiber yield and adaptability parameters in the conditions of North-West of the Russian Federation - A. D. Stepin; M. N. Rysev; T. A. Ryseva; T. D. Lisitskaya (Аграрная наука Евро-Северо-Востока, 2022)
Studies on the evaluation of 20 accessions of fiber flax of domestic and foreign selection according to flax fiber yield and adaptability parameters were conducted in 2018-2020 in the conditions of the Pskov region on sod-weakly podzolic light loamy soil. The Dobrynya variety (Russia), the yield of which depending on the year of testing was 215...273 g/m2, was used as standard. The most favorable conditions for fiber flax were in 2018 (Ij = +24.3), and stressful conditions caused by hot and dry weather during the critical period of plant growth and development (GTK = 0.83) - in 2020 (Ij = -30.8). The samples from China V 51267, 97192-79, y 7S12-13, Vuan 2009, M0269-1, wsh2-5-4 were characterized by the highest average fiber yield over the years of testing (259...275 g/m2) and yield under contrasting conditions (254...279 g/m2), with an average varietal of 232 and 230 g/m2, respectively. The varieties Hon Jku 350, Honkei 28 (Japan), L-1 Soglasie х Alfa (Russia), V 51267 (China) showed the lowest yield variability (7.0...10.8 %). The same samples were distinguished by higher stress resistance. According to homeostaticity (Hom), Hon Jku 350 (Japan), L-1 Soglasie х Alfa (Russia), V 51267 (China) were distinguished: 106.9; 98.9 and 52.1, respectively. Highly responsive to growth conditions (bi>1) were samples 97192-79 (1.93), 97192-79-8 (1.88) from China and L-3 Orshansky-2 x Tvertsa (1.74), Nadezhda (1.56) from Russia; plastic - Heiya 8(1.06), 92199-6-5(1.08) (China) and st. Dobrynya (1.01) (Russia), weakly responsive (bi < 1) -L-1 Soglasie х Alfa (Russia), Hon Jku 350, Honkei 28 (Japan). The best in stability (Gd2) samples were Heiya 8 (13) – China; L-3 Orshansky-2 x Tvertsa (26), L-1 Soglasie х Alfa (179), L-2 Voskhod х Zaryanka (182) - Russia; Hon Jku 350 (186) – Japan. According to the yield of flax fiber and the complex of adaptability parameters, based on the ranking, the cultivars L-1 Soglasie х Alfa (Russia), V 51267, wsh2-5-4, 97192-79 (China) with the greatest adaptive potential were identified. They can be used as sources of adaptability when creating new varieties of flax.